Analisis User Interface Situs Web Bappelitbangda Kabupaten Purbalingga - Resad Setyadi; Kholifatul Ainun Izzah (STMIK Budi Darma, 2023)
Sometimes on a website, which is mainly in the government, there is not enough attention to the design that is made, so that the appearance and contents inside are not well organized. A good user interface will make recommendations for admins in making appearances on the website, especially those owned by the Bappelitbangda Kab, Purbalingga website. The purpose of this study is to provide recommendations for an attractive web appearance to the admin to minimize data input errors made by the admin and make it easy for the public or other users to find out information on the Bappelitbangda Purbalingga web, with this analysis it can be useful as public knowledge to find out information in the area Purbalingga. Based on the results of the user interface analysis, Bappelitbangda Purbalingga website which was conducted by 15 employees using 7 aspects of the user interface, it was concluded that the average respondent stated that it was good. This was obtained based on the results of the data research questionnaire on each aspect of the user interface.